Prevalence of Functional Gastrointestinal Disorders according to Rome III Criteria in Italian Morbidly Obese Patients. (4th November 2013) - Santonicola, Antonella; Angrisani, Luigi; Ciacci, Carolina; Iovino, Paola
Abstract : The relationship between GI symptoms and obesity has yet to be completely clarified. Aim . To determine in a morbidly obese southern Italy adult population the prevalence of Functional Gastrointestinal Disorders (FGID) and its association with the presence of a Binge Eating (BE) behavior pattern. Methods . Consecutive obese patients eligible for bariatric surgery and 100 Healthy Controls (HC) were recruited. All participants were questioned and scored for the presence of FGID according to Rome III criteria and for the presence or the frequency-intensity of a number of upper and lower GI symptoms. BE behavior pattern was assessed. Results . One-hundred obese patients met the inclusion criteria. The prevalence of FGID was similar between obese patients and HC. There was a significant association between obese patients with BE behavior and postprandial distress syndrome (P = 0.04 ). Moreover, a significantly higher frequency-intensity score for epigastric fullness (1.23 ± 0.45 versus 0.35 ± 0.13, P = 0.01 ) was found in obese patients with BE behavior compared to obese patients without. Conclusions . Obese patients with a BE behavior pattern showed a significantly higher prevalence of postprandial distress syndrome. A greater knowledge of the GI symptoms associated with obesity along with the pathophysiological mechanisms underlying will be important in the clinical management of these patients.